2019
DOI: 10.1126/scisignal.aau1468
|View full text |Cite
|
Sign up to set email alerts
|

Muscle-generated BDNF is a sexually dimorphic myokine that controls metabolic flexibility

Abstract: The ability of skeletal muscle to switch between lipid and glucose oxidation for ATP production during metabolic stress is pivotal for maintaining systemic energy homeostasis, and dysregulation of this metabolic flexibility is a dominant cause of several metabolic disorders. However, the molecular mechanism that governs fuel selection in muscle is not well understood. Here, we report that brain-derived neurotrophic factor (BDNF) is a fasting-induced myokine that controls metabolic reprograming through the AMPK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(69 citation statements)
references
References 68 publications
5
63
0
Order By: Relevance
“…Interestingly, BDNF was recently identified to regulate and promote a glycolytic muscle fiber phenotype in young male mice [27]. However, in female mice, a lack of BDNF resulted in skeletal muscle metabolic myopathy and insulin resistance [28]. Further research is required to confirm and fully understand potential sex-specific associations and their underlying mechanisms between cardiorespiratory fitness, skeletal muscle function, and BDNF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, BDNF was recently identified to regulate and promote a glycolytic muscle fiber phenotype in young male mice [27]. However, in female mice, a lack of BDNF resulted in skeletal muscle metabolic myopathy and insulin resistance [28]. Further research is required to confirm and fully understand potential sex-specific associations and their underlying mechanisms between cardiorespiratory fitness, skeletal muscle function, and BDNF.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, these parameters were included as confounders. Further, very recently, BDNF was identified as sexually dimorphic neurotrophin [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al. [ 32 ] revealed that muscle-derived BDNF acts as a myokine and plays an important role in controlling energy metabolism. However, the clinical application of BDNF is greatly limited by its short half-life and non-bioavailable nature [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…During fasting or energy deficits, the skeletal muscles would adjust energy demands and preserve energy homeostasis [12]. Ours and other studies found that growth factors coordinate metabolic reprogramming in muscle during fasting [13].…”
Section: Introductionmentioning
confidence: 51%